Empowerment of Balinese Women Behind the Nyentana Tradition in Tabanan Regency - Ni Made Ari Cahyani; Ni Made Tisnawati; Putu Ayu Pramitha Purwanti; Anak Agung Istri Ngurah Marhaeni (Green Publisher Indonesia, 2026)
Decision-making in the household, including decisions made by women, affects consumption patterns because it determines the allocation of limited resources across various needs. This study analyses the influence of family income, work time allocation, education, and the role of parents on the decision-making of women and their daughters; the influence of these variables and decision-making on household consumption behaviour in Tabanan Regency; indirect influence through decision-making as a mediating variable; and the role of the Nyentana tradition in maintaining family assets and traditions. The study involved 30 women and daughters as respondents, with supporting informants including female family members, male family members (nyentana), the Tabanan Regency Customary Village Assembly, the Women and Children Empowerment and Protection Office, and NGOs and academics. The sampling technique employed accidental and snowball sampling. Data were collected through observation, structured interviews, and in-depth interviews. Analysis was carried out through descriptive analysis, path analysis, and descriptive narrative, accompanied by validity and reliability tests. The results show that family income, work time allocation, education, and parental roles have a positive and significant effect on decision-making, and a positive and significant effect on household consumption behaviour. Decision-making has been proven to mediate the influence of these variables on consumption behaviour. In addition, the nyentana tradition can serve as a strategy to address household challenges in maintaining the continuity of family lineage, the rebuttal of claims, and the ownership and management of family inheritance, so that these are not disrupted or transferred outside the family line.